Magnetically confined fusion plasma physics. - Zheng, Linjin (IOP ebooks. 2020 collection., 2020)
This second volume title presents a review of the state-of-the-art theory and application of magnetically confined plasma physics. The book covers three major topics: the Braginskii transport theory, the newly developed perpendicular magnetofluid theory, and the fluid-kinetic hybrid theories. In greater detail, the perpendicular magnetofluid theory is examined, along with the equilibrium and stability analyses. The book provides an advanced review on the state-of-the-art theory and application of magnetically confined plasma physics and is an essential reference for students and researchers in this field.